Keputusan Menjalin Hubungan/Kedekatan dengan Pasangan Beda Agama pada Gen Z - Sabila Ayu Amelia; Mayang Ariyani; Rauly Sijabat (INDO PUBLISHING, 2026)
Interfaith romantic relationships are increasingly found among Generation Z, particularly within Indonesia’s multicultural social context. Open-minded attitudes, frequent cross-cultural interactions, and the influence of digital environments encourage Gen Z individuals to engage in relationships that were once considered socially sensitive. Nevertheless, such decisions involve complex considerations, including religious values, family expectations, and internal emotional conflicts. This study aims to explore the decision-making process of Generation Z in forming relationships with partners of different religions, the influencing factors behind these decisions, and the strategies used to cope with emerging challenges. A qualitative approach with a phenomenological method was employed. Data were collected through in-depth interviews and observations of Gen Z individuals in Semarang who had experienced or were currently involved in interfaith relationships. The findings reveal that emotional attachment and personal compatibility are key factors in initiating these relationships, while concerns about religious principles and future commitment, especially marriage, become major challenges. The study highlights that although Generation Z tends to be more open toward differences, religious values and social support remain crucial determinants in the sustainability of interfaith relationships.